PELATIHAN PENGGUNAAN TEX-WORD DAN VISIO 2007 UNTUK MEMPERCEPAT PENULISAN RUMUS MATEMATIKA BAGI GURU-GURU DI SMPN 2 KUTA - Dharmawan, K.; Nilakusmawati, D.P.E. (Buletin Udayana Mengabdi, 2012)
The aims of this community service activity were to introduce the usage of TeX-Word and of Visio 2007 to quicken writing of mathematics formula to teachers of SMPN 2 Kuta and improve ability of teachers in writing of mathematical equation, as supporter in activity of compilation of academic writing in the form of module, lecture notes or book. This community service activity was executed to teachers at SMPN 2 Kuta. Method applied in this activity is in the form of training of writing the mathematics formula by using TeX-Word and of Visio 2007, with forwarding of material of training used presentation method, also practice directly by participant of training. Result of examination of hypothesis using t test obtained value of t is -11.235 with probability 0.000. Because probability < 0.05, hence Ho refused, meaning that giving of training of usage of TeX-Word and Visio 2007 having an effect by significant on to make-up of knowledge and ability of teachers as participant of training in writing mathematics formula quickly in SMPN 2 Kuta